Eksplorasi Konsep Geometri dalam Perspektif Etnomatematika pada Makanan Tradisional “Jaja Bali” (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2025)
This study aims to explore and identify geometric concepts embedded in traditional Balinese food, known as Jaja Bali, through an ethnomathematics perspective. A qualitative approach with an ethnographic method was employed, involving direct observation of various types of Jaja Bali found in traditional markets and local food stalls across several areas in Bali. Data were collected through descriptive field notes, informal interviews with vendors, and visual documentation to support the findings. The collected data were then analyzed using the interactive analysis model proposed by Miles and Huberman, which includes data reduction, data display, and conclusion drawing. The results reveal that Jaja Bali embodies a wide range of geometric concepts, encompassing both two-dimensional and three-dimensional shapes such as squares, circles, parallelograms, triangles, semicircles, and cylinders. In addition, concepts of symmetry and geometric transformations, particularly rotation, were also identified. These findings highlight that Jaja Bali is not only rich in cultural and symbolic value but also represents practical applications of geometric concepts in the daily lives of the Balinese community. This study is expected to serve as an alternative, culturally contextualized resource for teaching and learning geometry.